Socioecological resilience of typical citrus fruit agroecosystems - Cleves-Leguizamo, José Alejandro; Salamanca-Sanjuanes, Hernan; Martínez-Bernal, Liven Fernando (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
This paper, as a tool for analysis, considered the capacity of the interaction that open systems have against the occurrence of disturbances so that they can continue to function with minimal losses of energy, called resilience, an emerging characteristic of agroecosystems. To establish a method to measure this characteristic, ten variables were evaluated, including seven cultural variables: level of schooling, land tenure type, saving capacity, social organizational identity, farm infrastructure, weed control and production system; and three ecosystem variables: water resource availability, phytosanitary management and Main Agroecological Structure (MAS) in typical citrus fruit agroecosystems. These were methodologically grouped into six recommended domains: groups of farms and citrus growers with similar ecosystem and cultural conditions that have been characterized and typified in a previous study. In each of these groups, three farm types were selected for a total of 18 production units (department of Meta, Colombia). To determine the difference between the variables, Chi-square tests were applied (using the Pearson and Fisher statistics). Network analysis was applied to determine the relationship between the variables. The resilience was not significantly correlated with level of schooling, farm infrastructure or MAS. The relationship between the resilience and cultural variables presented a high significance, whereas the ecosystem variables showed a low statistical significance.